2011
DOI: 10.1074/jbc.m111.241901
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Control of Na,K-ATPase Activity and Cell Growth by a Splice Variant of FXYD2 Protein with Modified mRNA

Abstract: In kidney, FXYD proteins regulate Na,K-ATPase in a nephron segment-specific way. FXYD2 is the most abundant renal FXYD but is not expressed in most renal cell lines unless induced by hypertonicity. Expression by transfection of FXYD2a or FXYD2b splice variants in NRK-52E cells reduces the apparent Na ؉ affinity of the Na,K-ATPase and slows the cell proliferation rate. Based on RT-PCR, mRNAs for both splice variants were expressed in wild type NRK-52E cells as low abundance species. DNA sequencing of the PCR pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that FXYD2 is upregulated in cultured rat renal NRK-52E cells in response to hyperosmotic stress. 25 Interestingly, upregulation of full-length FXYD2 had a negative effect on cell growth in cultured NRK-52E cells. Expression of a mutant FXYD2 resulting in loss of the C-terminus, however, was associated with loss of inhibition of cell growth in culture.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that FXYD2 is upregulated in cultured rat renal NRK-52E cells in response to hyperosmotic stress. 25 Interestingly, upregulation of full-length FXYD2 had a negative effect on cell growth in cultured NRK-52E cells. Expression of a mutant FXYD2 resulting in loss of the C-terminus, however, was associated with loss of inhibition of cell growth in culture.…”
Section: Discussionmentioning
confidence: 98%
“…This alternative use of first exons has been suggested to play a role in posttranscriptional regulation of Fxyd2b transcripts. 14 Figure 3B shows two glutaminase (Gls) isoforms with alternative carboxyl-terminal amino acid sequences and 39-untranslated regions. The short isoform predominates in segments downstream from the proximal tubule, but the long isoform is more abundant in proximal tubule.…”
Section: Resultsmentioning
confidence: 99%
“…Its function is modulated by post-translational modification [16, 18], as well as by gene splicing and RNA editing, which respectively govern the expression of two splice variants, FXYD2a and FXYD2b, and of a truncated form of FXYD2b that is not exported to the plasma membrane [5, 13, 14, 21]. The two splice variants of FXYD2 have identical amino acid sequences, except in their N-terminal segments, encoded by the first exon [22, 23].…”
Section: Introductionmentioning
confidence: 99%